2012
DOI: 10.1161/hypertensionaha.112.193318
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Function and the Role of Oxidative Stress in Heart Failure, Heart Transplant, and Beyond

Abstract: Using flow-mediated vasodilation (FMD), reactive hyperemia (RH), and an acute oral antioxidant cocktail (AOC [Vitamin C, E and α-lipoic acid]), this study aimed to provide greater insight into altered vascular function and the role of oxidative stress in chronic heart failure patients with reduced ejection fraction (HFrEF) and at several time points beyond heart transplantation (HTx). A total of 61 age-matched subjects (12 healthy controls, 14 NYHA Class II and III HFrEF patients, and 35 HTx recipients (< 3 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 64 publications
(68 reference statements)
9
36
2
Order By: Relevance
“…Our group has recently demonstrated that patients with HFrEF have reduced FMD, but not post occlusion RH, compared with healthy age-matched controls. 7 These data suggest that, in contrast to our current findings in HFpEF, conduit artery impairments alone contribute to the vascular dysfunction in HFrEF. This discrepancy between disease-related changes in the conduit and microvascular segments of the peripheral circulation may partially explain why many of the therapeutic approaches that have proven so successful in patients with HFrEF are somewhat less efficacious in the patient group with HFpEF.…”
Section: The Distinct Vascular Pathology Of Hfpefcontrasting
confidence: 96%
See 2 more Smart Citations
“…Our group has recently demonstrated that patients with HFrEF have reduced FMD, but not post occlusion RH, compared with healthy age-matched controls. 7 These data suggest that, in contrast to our current findings in HFpEF, conduit artery impairments alone contribute to the vascular dysfunction in HFrEF. This discrepancy between disease-related changes in the conduit and microvascular segments of the peripheral circulation may partially explain why many of the therapeutic approaches that have proven so successful in patients with HFrEF are somewhat less efficacious in the patient group with HFpEF.…”
Section: The Distinct Vascular Pathology Of Hfpefcontrasting
confidence: 96%
“…Although vascular dysfunction, assessed by FMD, has been well documented in patients with HFrEF, [4][5][6][7] and is an independent risk factor for an increased risk of clinical events and poor prognosis in this cohort, 4 much less is known about vascular function in the HFpEF population. In the current study, we observed a reduction in brachial artery FMD in patients with HFpEF compared with controls (figure 1), which initially seemed to indicate impaired conduit vascular function in this patient group.…”
Section: Conduit Vessel Vascular Function In Hfpefmentioning
confidence: 87%
See 1 more Smart Citation
“…However, it should be noted that the single PLM model, which greatly reduces the stimulation of the group III mechanoreceptors as evidenced by the lack of a HR response in either subject group, also revealed that the FBF response in the HFrEF was still greatly attenuated. In combination, these data are consistent with the fact that impaired endothelium-dependent vasodilation has long been associated with many cardiovascular diseases, including HF [30, 31], but extends these findings to movement-induced hyperemia, uncomplicated by changes in metabolism. Utilization of the single PLM removed the influence of the persistent mechanical stimulus associated with continuous movement of the leg.…”
Section: Discussionsupporting
confidence: 84%
“…Previously it has been documented that an acute antioxidant cocktail (AOC) of known efficacy 33, 34 is capable of improving vascular function, as assessed by FMD, in the elderly population 33 and heart transplant recipients with history of heart failure 35 , populations with increased CVD risk and a definitive incident, respectively. The AOC-induced improvement in redox balance 36 likely attenuates free radical mediated reductions in nitric oxide bioavailability, thus increasing endothelial dependent flow mediated dilation 3335 .…”
Section: Introductionmentioning
confidence: 99%